Development and Implementation of an LCMV Adaptive Beamforming Antenna Using USRP and GNU Radio - Khang Nguyen Viet Thai,; Khanh Nguyen Tuan,; Thuyet Nguyen Vo That, (Journal of Technical Education Science, 2025)
This present paper introduces the development and implementation of the Linearly Constrained Minimum Variance (LCMV) adaptive beamforming antenna system with two Universal Software Radio Peripheral (USRP) boards to receive and transmit the processed data through GNU’s Not Unix (GNU) Radio Companion software. The collected data will then be displayed through an external dashbased Visual Studio Code Program in order to accurately measure the performance of the LCMV beamforming algorithm while being compared with the conventional antenna system (Delay-and-Sum). The comparison criteria of the performance metrics between the 2 systems in this paper are: White Noise Gain (WNG), Null Depth, Interference Suppression, and Half-Power Beam Width (HPBW). The Flowgraph, which represents the logic of the two antenna systems in GNU Radio Companion (GRC), is subjected to noise interference to further reflect their performance in real-world settings. The research also demonstrates a clear difference in the performance between the two antenna system models, establishing a foundation for developing digital twin-based communication systems that enable continuous monitoring, simulation, and optimization in future wireless networks.